PENERIMAAN DIRI PADA REMAJA DENGAN DIABETES TIPE 1 DI KOTA MALANG - Ispriantari, Aloysia; Priasmoro, Dian Pitaloka (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
Type 1diabetes is the most common chronic disease of children and adolescents inthe world. Adolescents with type 1 diabetes require more complex diabetes managementthan children and adults. Acceptance of their condition is needed for optimum the qualityof life. The purpose of this study was to describe self-acceptance in adolescents with type1 diabetes.The method on this study was descriptive. The samples were all adolescentsaged 10-19 years who joined IKADAR (Ikatan Diabetesi Anak dan Remaja) in MalangCity, which were 24 children. The variable of this study was self-acceptance measured byBerger's Self Scale Acceptance questionnaire and then analyzed and presented in theform offrequency distribution and percentage. The results were mean score was 44.25 soit can be condludes that adolescents with type 1 diabetes has a good self-acceptance. Itwas influenced by emotional maturity, good social support and long suffering fromdiabetes.